Supporting the transition from weight loss to maintenance: development and optimisation of a face-to-face behavioural intervention component - Sainsbury, K.; Cleland, C.; Evans, E.; Adamson, A.; Batterham, A.; Dombrowski, S.; Gellert, P.; Hill, M.; Kwasnicka, Dominika; Scott, D.; Sniehotta, F.; White, M.; et al. (Routledge, 2017)
After weight loss, most individuals regain lost weight. Interventions to support the transition from successful loss to weight loss maintenance (WLM), regardless of the method of prior weight loss, are needed. The aims of this study were to (1) develop a face-to-face behavioural intervention session to support overweight and obese individuals who have recently lost a clinically significant amount of weight in the transition to WLM; (2) to assess the single-session intervention for acceptability and feasibility prior to its use in a larger, 12-month, multi-component trial; and (3) to optimise the intervention session for future use based on participant feedback. Participants with a Body Mass Index of ≥25 kg/m2 prior to a ≥5% weight loss in the previous 12 months were recruited via the local government authority and community-based advertisements. Each attended the one-hour session with a trained facilitator, which focused on setting maintenance-relevant weight, eating, and physical activity goals. Semi-structured interviews were carried out immediately post-session to obtain feedback on the acceptability of this intervention component. Data were used to generate recommendations for changes to the session, which were discussed by the team, and used to optimise the session. Seventeen participants (13 female; median WL = 13%) were recruited.All participants evaluated the intervention session positively; 11 participants suggested improvements including reducing information provision in favour of greater focus on identifying and coping with barriers, and the inclusion of practical examples. The systematic refinement and optimisation process resulted in an acceptable and feasible face-to-face behavioural intervention session (described here), which will be tested as part of a multi-component intervention. We anticipate the session could be used to supplement existing support including online services, and has the potential to benefit people who have lost a clinically significant amount of weight to achieve WLM over the long term.